Diversity of Butterfly (Rhopalocera) in The River Flow Area at Taman Hutan Raya Sesaot as an Enrichment of Animal Ecology Practicum Materials - Rawindy Aulia Hapsari; Agil Al Idrus; Mohammad Liwa Ilhamdi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The butterfly is one of the insects type that originated from the order of lepidoptera, which having scaly wings. The scales is what gives pattern on the butterfliesÃ¢â¬â¢ wings. In ecosystems, butterflies serves as a pollinator that helps plants to reproduce. Besides, butterflies like the environment that is close to the river flow. Thus allowing the possibility of butterflies activities in the surrounding area over the river flow at Taman Hutan Raya Sesaot. The research is aimed to identify species of butterflies (suborder Rhopalocera) and to determine the level of diversity of butterflies in the river flow areas at Taman Hutan Raya Sesaot. This research is carried out from January until February 2021 in the river flow area at Taman Hutan Raya Sesaot. Conducted in three points, namely the path of water 1, the path skirting the woods and pathways of water 2. The methods of taking samples of butterflies conducted by purposive survey method. The mechanical technic of taking samples is done by using nets insects. Analysis of butterfly diversity index obtained diversity index (H') and index of dominance (D). Analysis of butterfly diversity index obtained diversity index (H') for all species, namely 2.29 (medium category). Analysis index of dominance obtained index of dominance for the entire species, namely 0.13 (relatively low). Based on the results of the research, the writer found 16 species (164 individuals) that were included into the four families of Papilionidae, Nymphalidae, Pieridae and Lycaenidae.